Knowledge, attitude, and practice regarding voluntary whole-body donation among medicos in Northeast India - Nabarun Karmakar; Tamal Chakraborty; Anjan Datta; Kaushik Nag; Snigdha Das; Partha Bhattacharjee (Wolters Kluwer Medknow Publications, 2020)
Background: Voluntary whole-body donation is an important source of cadavers for anatomical study and research. As the medicos are intimately related to this, they should play vital role in the body and organ donation. Objective: The objective of the study was to assess knowledge, attitude, and practice (KAP) regarding voluntary whole-body donation among medicos in Northeast India. Methodology: This cross-sectional study was conducted among 361 medicos in Northeast India from March 2018 to June 2018. A pretested, semi-structured questionnaire was used to collect the required information on KAP regarding voluntary whole-body donation. The collected data were entered in SPSS version 16.0 and represented in proportions, and P < 0.05 was considered as statistically significant. Results: Most of the medicos (88.1%) knew about voluntary whole-body donation, and 60.7% of the respondents even replied that body should be brought to medical institute within specific time after death. Half of them (50.1%) got information from mass media, 10.8% from nongovernmental organizations, and 35.2% from doctors. Maximum (83.7%) agreed that body donation is useful for society, whereas 6.4% did not agree. Only 24.4% of the respondents had seen "donor card pledge form," whereas only 7.5% (n = 27) were currently registered as a voluntary body donor. Conclusion: We found poor knowledge and attitude regarding various facets of voluntary whole-body donation; practice was even dismal among participants. Media and doctors being major source of information should spread the idea of voluntary whole-body donation that it is better to donate body after death, for research in medical education rather than cremation.